Heterogeneities in the Production of Urbanization, and Urban Services in Latin America - Pírez, Pedro (Universidad del Rosario, 2020)
This article proposes a conceptual framework to study urban services as part of capitalist urbanization, its contradictions and the state and social processes of decommodification. It tries to link the reproduction of capitalism and the particular conditions of the population excluded from access to market consumption and the state interventions to address those needs: Such state interventions include non-market and decommodified terms predominantly oriented to urbanization consumption. This article seeks to explain the importance of non-market and social decommodified urbanization (popular production of habitat) as well as the presence of reverse urbanization in the dependent capitalism in Latin America.